Tren Global Stunting dalam Satu Dekade Terakhir: Analisis Bibliometrik: Global Trend of Stunting in The Last Decade: A Bibliometric Analysis - Deda, Yohanis Ndapa; Nahak, Maria Paula Marla; Pala, Aplonia (Amerta Nutrition, 2024)
Background: Stunting is a growth and development problem in children caused by chronic malnutrition and disease. There is no bibliometric analysis related to stunting globally and simultaneously using metadata from GS (Google Scholar) and Scopus on Vosviewer visualization from 2012 to 2022. Objectives: To study the trends in research on stunting through a bibliometric analysis of the widely used GS and Scopus databases. Methods: This method was used to investigate and evaluate a large amount of scientific data on stunting, revealing the intricacies of the evolution and novelties related to stunting over a decade (2012-2022). Discussions: Stunting studies have increased over the last decade (2012-2022). The authors most cited based on the Scopus database are Prendergast & Humphrey. The authors most cited based on the GS database is de Onis & Branca. The productive author based on GS is T Siswati from Indonesia. The top numbers one influential author based on Scopus are M. De Onis and P. Svefors. The total number one source article based on Scopus and GS is Plos One. PH Nguyen, P Menon, and VM Aguayo are the three authors who have co-authored the most documents related to stunting in the past decade based on VosViewer visualizations. Based on the results of the VosViewer visualization, six significant clusters were also discussed: review, Inequality, Ethiopia, anemia, trial, and Infant. Conclusions: Stunting prevention in areas or countries with acute stunting needs more detail from governments and WHO. We recommend that future research on the pattern of appropriate policies to prevent stunting be carried out.